P226 The Changing Face of Home NIV (Non Invasive Ventilation). (19th November 2012) - Fletcher, SV; Ewles, S; Wilkinson, JE
Abstract : Introduction: The number of patients requiring home NIV for chronic hypercapnic respiratory failure is rising and the indications are changing. This has significant service planning and cost implications. Methods: A retrospective review of the database of all patients established on home NIV since 2004 was conducted. All clinical records from these patients were reviewed. The indication for NIV was classified as thoracic cage abnormalities, neuromuscular disease, OHS (obesity hypoventilation syndrome +/– obstructive sleep apnoea), COPD (chronic obstructive pulmonary disease), CF(cystic fibrosis) and ILD (interstitial lung disease)/other. The date of death was gained from the internal hospital records (eDocs) and through the NHS portal with the use of individual NHS numbers. Results: There were 286 patients established on home NIV between 2004 and 2012, 162 were male, the overall mortality was 29%. There has been over a seven fold increase in the yearly prevalence of patients requiring home NIV and the indication for its use is changing over time (figure 1 ). The proportion of patients with thoracic cage abnormalities is reducing from 25% in 2004 to 11% in 2012. The use of NIV for obesity hypoventilation syndrome has increased 10 fold since 2004. This hospital is the regional neurosciences referral unit which may explain the large number of patients requiring NIV for neuromuscular disease, 45% of which had motor neurone disease. In 2004, the cost of setup with an NIV machine and consumable for a all new patients, plus the cost of consumables for those established on NIV was estimated to be £73, 000; whereas this cost in 2011 was estimated to be £308, 500 (incl VAT). This does not include the cost of personnel. Conclusion: This study highlights the changing face of home NIV service in terms of both the increasing numbers of patients requiring home NIV and the changing pattern of indication, particularly in the face of an emerging obesity epidemic.